Effects of anionic surfactant on n-hexane removal in biofilters. (May 2016) - Cheng, Yan; He, Huijun; Yang, Chunping; Yan, Zhou; Zeng, Guangming; Qian, Hui
Abstract: The biodegradability of three anion surfactants by biofilm microorganisms and the toxicity of the most readily biodegradable surfactant to biofilm microorganisms were examined using batch experiments, and the optimal concentration of SDS for enhanced removal of hexane was investigated using two biotrickling filters (BTFs) for comparison. Results showed that SDS could be biodegraded by microorganisms, and its toxicity to microorganisms within the experimental range was negligible. The best concentration of SDS in biofiltration of n-hexane was 0.1 CMC and the elimination capacity (EC) of 50.4 g m −3 h −1 was achieved at a fixed loading rate (LR) of 72 g m −3 h −1 . When an inlet concentration of n-hexane increased from 600 to 850 mg m −3, the removal efficiency (RE) decreased from 67% to 41% by BTF2 (with SDS) and from 52% to 42% by BTF1 (without SDS). SDS could enhance hexane removal from 43% (BTF1) to 60% (BTF2) at gas empty-bed residence time (EBRT) of 7.5 s and an inlet concentration of 200 mg m −3 . Highlights: The biodegradability of 3 surfactants by biofilm microorganisms was evaluated. SDS could be biodegraded by and was not toxic to biofilm microorganisms. The optimal SDS concentration for enhanced n-hexane removal in biofilters was 0.1 CMC.